2017
DOI: 10.1111/ajco.12748
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic triple negative breast cancer: Optimizing treatment options, new and emerging targeted therapies

Abstract: Triple negative breast cancer (TNBC) is a heterogeneous disease, not only on the molecular level, but also on the pathologic and clinical levels. It also has a distinct epidemiology. TNBCs are frequently of high histologic grade, typically more aggressive and difficult to treat than hormone receptor-positive tumors, and they are associated with a higher risk of early relapse with visceral metastasis after surgery, chemotherapy and/or radiotherapy. The lack of estrogen receptor, progesterone receptor and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 60 publications
0
68
0
4
Order By: Relevance
“…The high BC mortality rates in women of African ancestry (WAA) despite having lower incidence rates and lifetime risks of BC than Caucasian women, initially led many to think that this disparity was linked to socio-economic status [9397]. However, several studies now suggest that genetic risk factors/predisposition contribute to the racial disparity in the prevalence and mortality of patients diagnosed with the TNBC subtype [95, 97, 98]. Hence, the recent discovery that high Kaiso expression correlates with aggressive BC subtypes like TNBC and shorter metastasis-free survival in WAA [13, 81], as well as with aggressive PCa in African American (AA) men [14] suggests that high Kaiso expression may be linked to the racial disparity in prevalence and/or outcomes of aggressive cancers in people of African ancestry.…”
Section: Kaiso and Racial Disparities In Cancermentioning
confidence: 99%
“…The high BC mortality rates in women of African ancestry (WAA) despite having lower incidence rates and lifetime risks of BC than Caucasian women, initially led many to think that this disparity was linked to socio-economic status [9397]. However, several studies now suggest that genetic risk factors/predisposition contribute to the racial disparity in the prevalence and mortality of patients diagnosed with the TNBC subtype [95, 97, 98]. Hence, the recent discovery that high Kaiso expression correlates with aggressive BC subtypes like TNBC and shorter metastasis-free survival in WAA [13, 81], as well as with aggressive PCa in African American (AA) men [14] suggests that high Kaiso expression may be linked to the racial disparity in prevalence and/or outcomes of aggressive cancers in people of African ancestry.…”
Section: Kaiso and Racial Disparities In Cancermentioning
confidence: 99%
“…However, TNBC is best considered as an umbrella term, encompassing a wide spectrum of entities with distinct genetic, transcriptional, histological and clinical differences. [1][2][3] As a group, TNBC is associated with high proliferation, early recurrence and poor survival rates. 2 4 This aggressive disease is resistant to widely used targeted therapies such as trastuzumab and endocrine therapies, which have been effective at reducing breast cancer mortality.…”
Section: Introductionmentioning
confidence: 99%
“…2 5 There are very limited and often ineffective treatment options for patients with poor prognosis (chemoresistant and late-stage/metastatic) TNBC. 2 Recent large-scale gene expression profiling and immunohistochemistry (IHC) analyses reveal that TNBC may be the most regulated by tumor-infiltrating lymphocytes (TILs) and thus the most responsive to immunotherapies compared with other breast cancer subtypes. 6 7 In addition, accumulating data suggest that certain chemotherapeutic drugs such as anthracyclines mediate their anti-cancer activity through direct cytotoxic effects and also through activation of TIL responses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we observed that paclitaxel, unlike SSA, increased p-AKT expression in lung tissue and exhibited lower inhibiting efficacy on TNBC lung metastasis than did SSA in the 4T1 mouse model. Wen et al (33) also reported the up-regulation effect of paclitaxel on p-AKT, which suggests a possible mechanism for the relatively poor overall survival of patients with metastatic TNBC treated with paclitaxel (34).…”
Section: Discussionmentioning
confidence: 94%